Video-assisted thoracoscopic surgery and open chest surgery in esophageal cancer treatment: present and future - Depypere, Lieven (J Vis Surg, 2017)
Surgical esophageal cancer treatment has, like other solid organ cancer treatments, evolved from a monospeciality treatment towards a multidisciplinary treatment. In an increasing number of centers around the world minimally invasive esophagectomy (MIE) is now proposed as the preferred surgical approach although there is still a place for open surgery in selected cases. Careful assessment of oncologic and medical operability and adequate pre-operative preparation are the first and foremost important steps to guarantee optimal oncological and functional results. This article serves as a practical guide to MIE for esophageal cancer with figures, equipment preference cards and videos explaining and illustrating a MIE procedure in prone position as one example of the present state of the art. Some future perspectives will also be discussed.